The Influence of Neoadjuvant Chemoradiotherapy on Muscle Mass in Patients with Rectal Cancer - Gregory Simpson; Thomas Marks; Sarah Blacker; Conor Magee; Jeremy Wilson (World Journal of Colorectal Surgery)
Background: The psoas major muscle accurately represents overall skeletal muscle mass. The skeletal muscle mass volume is related to outcomes in multiple surgical procedures including colorectal cancer. However, neoadjuvant chemoradiotherapy for rectal cancer may adversely affect muscle mass. Objective: Assess the effect of neoadjuvant chemoradiotherapy on muscle mass in rectal cancer patients as well as on outcomes. Design: Retrospective study. Setting: A large UK District General Hospital. Patients and Methods: Analysis of all rectal cancer patients between 2014 and 2017. Psoas major was measured at the L3 level using pre- and post-neoadjuvant chemoradiotherapy images. Psoas major to L3 cross-sectional area (PML3) was calculated for each patient. Main Outcome Measures: 30-day and 90-day mortality, inpatient stay, and postoperative complications. Sample Size: One hundred and twenty-one rectal cancer patients. Results: Median age was 72 years (IQR: 64–78 years). Male:Female ratio was 82:39. 30-day mortality was 0%, and 90-day mortality was 0.83%. Sixty-one patients underwent neoadjuvant chemoradiotherapy (50.4%). Thirty-one patients underwent abdominoperineal excision of the rectum (APER) (25.6%), 1 underwent proctocolectomy (0.83%), 1 underwent completion proctectomy (0.83%), and 88 patients underwent anterior resection (72.7%). Significant muscle loss occurred during neoadjuvant therapy (median loss: 25.9%, IQR: 12.6–36.8%) (P < 0.0001). No correlation was observed between PML3 and inpatient stay. Patients with PML3 in the lowest quartile had a chest infection rate of 11.1% and a complication rate of 37.1% rather than 6.2% and 26.8%, respectively, for those in the upper quartiles. Anastomotic leak rate in the PML3 lowest quartile was 23.5% compared to 11.4% in patients in the upper quartiles. Conclusion: Patients who received neoadjuvant chemoradiotherapy had a significant reduction in muscle mass. Muscle mass loss can be overcome with a prehabilitation program that may reduce muscle loss and improve outcomes. Limitations: Due to a low event-rate of anastomotic leak, it is difficult to show statistical significance with a patient cohort of this size. Conflict of Interest: None.